TG/HDL-C ratio as a risk marker for metabolic syndrome and atherosclerosis in adolescents aged 15-18 years in Indonesia - Dwi Sarbini; Siti Zulaekah; Sudrajah Wirajati Kisnawaty; Farida Nur Isnaeni; Winda Wahyu Pratiwi; Maya Sukmawati; Sharla Apsarini (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Metabolic syndrome is characterized by high levels of triglycerides, blood glucose, and blood pressure, along with low high-density lipoprotein cholesterol (HDL-C) and central obesity. The TG/HDL-C ratio is a quick and cost-effective marker of dyslipidemia and insulin resistance, increasing the risk of atherosclerosis. However, most studies on TG/HDL-C ratio in Indonesia have been limited to adolescent populations with distinct metabolic profiles and health risks. This study aimed to assess the correlation between metabolic syndrome risk and TG/HDL-C ratio as a marker of atherosclerosis risk in adolescents. This cross-sectional study was conducted at Batik 1 Senior High School Surakarta from October 2023 to March 2024. A total of 65 adolescents were selected using simple random sampling. The observed data included body mass index (BMI), waist circumference, blood pressure, fasting blood glucose, triglycerides, HDL-C, metabolic syndrome risk, and atherosclerosis risk. Pearson and Spearman correlation tests were used for statistical analysis. The results showed A significant correlation was observed between TG/HDL-C ratio and atherosclerosis risk (p= 0,000), waist circumference (p= 0,009), systolic blood pressure (p= 0,001), and diastolic blood pressure (p= 0,000). However, no significant correlation was found between fasting blood glucose level (p= 0,905) and BAZ (p= 0,405). In conclusion, TG/HDL-C ratio can serve as a valuable indicator for assessing metabolic syndrome risk in adolescents, allowing for early intervention to reduce the risk of atherosclerosis.